The complete mitochondrial genome of the Gongxi chicken and its phylogenetic analyses. Issue 1 (2nd January 2019) - Yan, Hai-Feng; Lin, Qian; Jiang, Gui-Tao; Pu, Xue-Hui; Dai, Qiu-Zhong; Zhang, Xu
Abstract: Gongxi chicken (GXC) is one of the famous indigenous breed of Hunan province in China. It is the first time that the complete mitochondrial genome sequence of the GX was reported. The total length of the mtDNA is 16, 783 bp. It contains the typical structure, including 22 transfer RNA genes, 2 ribosomal RNA genes, 13 protein-coding genes, and 1 noncoding control region (D-loop region). The overall composition of the mtDNA was estimated to be 30.30% for A, 23.75% for T, 32.48% for C and 13.47% for G. Phylogenetic analyses using N-J computational algorithms showed that the analyzed 26 Galliformes species are divided into four major clades: Phasianidae, Numidiidae, Odontophoridae and Megapodiidae. In addition, our work confirmed that GXC and Dongan yellow chicken (DYC), Taoyuan chicken and Dongan black chicken have a close genetic relationship with fellow tribal members Xuefeng black-boned chicken and Huang Lang chicken. Meanwhile, we also found that GXC and DYC have highly similar genetic relationship. This work will provide an important data set for the study in genetic mechanism of chicken in Hunan province.